Una especie nueva de Tillandsia (Bromeliaceae) de Guerrero, Mexico - Flores Cruz, M.=700 1 Diego Escobar, M.V.
(Es, En)
ilus. 15 ref
Keywords: BOSQUE DE CONIFERAS; EPIFITAS; TILLANDSIA; MEXICO; BOSQUE MESOFILO DE MONTAÑA; TILLANDSIA FASCIFOLIA; BOLETIN DE LA SOCIEDAD BOTANICA DE MEXICO